2022
DOI: 10.21203/rs.3.rs-980430/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaps in neonatal thermal care in low-resource settings: A web-based survey of healthcare workers.

Abstract: Background: Hypothermia has been widely regarded as a major contributory factor to neonatal mortality and morbidity in low-resource settings. Despite the recognition of the importance of thermal care for neonates a century ago and the established WHO guidelines, a high prevalence of neonatal hypothermia is still regularly reported. Hypothermia is avoidable in the majority of neonates because it is not a complication of prematurity but more the result of inadequate thermal care. The objective of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This was likely due to earlier recognition, clinical diagnosis and better treatment with the establishment of the nursery. Recent studies in similar contexts with neonatal nurseries have suggested that multidisciplinary approaches such as antibiotic stewardship, hygiene and protocols for feeding are necessary to further reduce the burden of sepsis in preterm infants [47,48,49], which can be extrapolated to full-term infant sepsis prevention. Future interventions might include improved diagnostics, empiric antibiotic treatment when sepsis is clinically suspected, and improved patient observation [49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was likely due to earlier recognition, clinical diagnosis and better treatment with the establishment of the nursery. Recent studies in similar contexts with neonatal nurseries have suggested that multidisciplinary approaches such as antibiotic stewardship, hygiene and protocols for feeding are necessary to further reduce the burden of sepsis in preterm infants [47,48,49], which can be extrapolated to full-term infant sepsis prevention. Future interventions might include improved diagnostics, empiric antibiotic treatment when sepsis is clinically suspected, and improved patient observation [49][50].…”
Section: Discussionmentioning
confidence: 99%
“…One limitation in Neno District is the lack of rst-trimester antenatal ultrasound dating with the need for postnatal determination of neonates who are preterm versus low birth weight. If postnatal dating of neonates is not completed, especially within 24 hours of admission, using birth weight or maternal or health care worker reports of the number of months pregnant mentorship, standardized protocols, and essential equipment and medicine availability, as demonstrated in other studies[46][47][48][49].The health care provider inputs re ected several changes that occurred. They reported that the most important change was increased capacitated staff in study period II and even more so in period III due to dedicated mentorship.…”
mentioning
confidence: 99%